Assessing the leaching of hazardous metals from pharmaceutical wastes and their ashes. Issue 2 (February 2015) - Gerassimidou, Spyridoula; Komilis, Dimitrios
The purpose of this research was the determination of the leaching potential of eight hazardous metals from expired pharmaceutical wastes and their ashes obtained after simulated incineration. A standardized leaching test (EN 14429) was used to assess leaching over a range of pH and comparison with the limits included in Decision 2003/33/EC was done at liquid/solid ratio 10. The goal was to assess the environmental impacts of pharmaceutical wastes after different disposal techniques (direct landfilling, incineration). A 3-year old composite sample of expired pharmaceutical wastes (drugs) was obtained and was separated into solid and liquid drugs. The packaging from each type of drug was also removed and tested separately, whilst the solid drugs and their packaging were incinerated at 900°C. Leaching tests on all solid substrates (solid drugs, packaging, ashed drugs, ashed packaging) were performed over a wide range of pH. The experiments showed that ashed drugs leached the highest amounts of all metals, except iron, and should be disposed of to a hazardous waste landfill, since Cd, Ni, and Pb exceeded the corresponding limits. Raw expired drugs, raw and ashed packaging did not exceed the pertinent limit values and could be, thus, disposed of directly to a non-hazardous waste landfill. In all experiments, the highest leaching potential (>90% of the total metal content) was measured at acidic pHs (<4). The leachable concentration of all metals increased as pH decreased, whilst Zn observed a small re-dissolution in the alkaline range.